ANALISIS PERHITUNGAN, PENYETORAN, DAN PELAPORAN PPH PASAL 21, PPH PASAL 22, PPH PASAL 23 DAN PPH PASAL 25 PADA PT. UND TAHUN 2021 - Feliciayulitania, Feliciayulitania; Widjaja, Purnamawati Helen (Jurnal Paradigma Akuntansi, 2024)
UND is one of the non-open companies that deals in chemicals. This company's been operating for 30 years Using technological systems in keeping with the development of The Times and the good organizational structure, pt. Und has been able to compete and survive with competitors until now. The study aims to find out the analysis and income tax calculations of 2021 through data obtained by direct writers from the company, so all available data is complete with evidence. Besides knowing the tax analyses and calculations, the study is also aimed at knowing whether companies follow government regulations or not when it comes to accounting, deposits, and reporting PPH chapters 21, chapter 22, chapter 23, and chapter 25 2021. The types and data sources used by the author are the primary data with data techniques that interview methods and data obtained from descriptive analysis.